RANCANG BANGUN MESIN PERAJANG WORTEL MENGGUNAKAN MESIN 1⁄2 HP - Andry Lesmana; Eka Sari Wijianti; , Saparin (Universitas Tridinanti Palembang, 2019)
The culinary industry is a strategic sector for economic development in Indonesia. in the province of Bangka Belitung Islands, now this has been done many culinary business home users better known business with catering. The culinary preferred to official events such as the wedding is one of the gado gado. The gado gado made with various mixtures ingredients like cucumber, carrots, cabbage and salad leaves. The process of cut carrots can be quite complex. Manually, the process of cutting carrots started with cut carrots into thin-thin, then cut extends so that the measuring length of approx. 7cm and thick 2-4 mm. For 5 kg of carrots, takes approximately 2 hours with 4 people of labor. By because it made the chopper engine carrots to help the culinary production to execution more efficient. The chopper engine carrots made dimension 900 mm x 530 mm x 400 mm, with motor power ½ Hp, and audible 1400 rpm. Cutting system using the rotary system namely the dish/stand eye cut the rotating while the position of the carrot is silent. The torque on the axis of the cutter 635,8325 Nmm. The research results show that to chop 1 kg carrot takes approximately 6-7 minutes. Now the results obtained are as much as 53,075% chopping results carrot is good or in accordance with the size of the expected, as much as 28,975 % showed good enough, 17,95 % less good. Keywords: Carrots, Chopper Engine carrots, Chainsaws